ANALISIS BIAYA KUALITAS DALAM MENINGKATKAN EFISIENSI BIAYA PRODUKSI PADA PT ACEH MEDIA GRAFIKA TAHUN 2012-2016 - Aditya, Tasya Meisheilla; BZ, Fazli Syam (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
This research is designed as a quantitative descriptive research approach. The research is aimed to analyze the quality cost applied by PT Aceh Media Grafika in addressing appropriate production cost of Serambi Indonesia in 2012 to 2016. On the other hand, the research is also aimed to analyze the effect of applied quality cost to the production cost efficiency in 5 years. The subject of this research is PT Aceh Media Grafika, while the object is the quality cost applied by the company. The data is analyzed by looking at the correlation of quality cost in increasing the efficiency of the production cost. This research used a simple correlation analysis that commonly knows as pearson correlation. The method used in collecting the data is mostly from documentation and literature review. The result shows that PT Aceh Media Grafika has not applied any specific calculation of quality cost, it has generally included in production cost.Based on the research analysis, the quality cost can possibly increase the efficiency of production cost. However it plays a very small roles because the quality cost is just a part of the whole production cost spent by the company.